Simultaneous Determination of Caffeine and Paracetamol by Zero-Crossing Second Derivative Spectrophotometry in Pharmaceutical Preparations - Tavallali, Hossein; Salami, Maryam (Asian Journal of Chemistry, 2010)
A second-derivative spectrophotometric method is described for simultaneous determination of caffeine and paracetamol. All measurements for made at the zero-crossing wavelengths at 260.0 nm for paracetamol and 288.0 nm for caffeine. Calibration graphs were linear over the range 0.1-30.0 mg/L for paracetamol and 0.1-20.0 mg/L for caffeine. The detection limits achieved were 0.095 mg/L for caffeine and 0.090 mg/L for paracetamol. The method is able to determine caffeine to paracetamol ratio 40:1 to 1:12 (w/w), accurately. Accuracy and reproducibility of determination method for the various known amounts of caffeine and paracetamol in their binary mixtures were tested. The proposed methods were suitably applied to assay of pharmaceutical preparations.